Enhanced Ozone Aging Resistance of Natural Rubber with 2-Mercaptobenzothiazole as the Constant-Viscosity Agent - Juan Zhou; Peng Deng; Hongxing Gui; Junxiao Xu; Jianhe Liao; Aiwu Ding (Journal of Chemistry)
For the actual storage and serving, a phenomenon of hardening and cracking always occurs in the natural rubber (NR), which sharply reduces the mechanical performance and hinders the further application of NR. Recently, some type of constant-viscosity agent has played a key role to be used for the treatment of NR, especially for the effect of ozone aging resistance. In this study, 2-mercaptobenzothiazole (MBT) was introduced into NR, and the constant viscosity and ozone aging resistance of NR with different contents of MBT were investigated using an accelerated storage experiment and an ozone aging experiment, respectively. The results indicated that the addition of MBT could improve the constant viscosity of NR in a certain degree. With the MBT content of 0.15%, NR/MBT-0.15 obtained a best ozone aging resistance and maintained the original high tensile strength. Therefore, it provided a promising route to design and prepare NR with high-quality ozone aging resistance.